Mechanical property optimisation of materials by nanostructuring: reduction of residual compressive stress in ta-C film - Lee, CS; Lee, KR; Suh, SH (TAYLOR & FRANCIS LTD, 2004)
Optimisation of the mechanical properties of a tetrahedral amorphous carbon (ta-C) thin film was attempted by nanostructuring. In this study, nanoscale multilayer films of ta-C and Si incorporated ta-C:Si layers were prepared. The residual compressive stress of the multilayer films decreased drastically without a decrease in the hardness and elastic modulus, compared with the monolithic films. No significant change in the atomic bond structure was observed in Raman spectral analysis. The present results thus provide a new possibility of application of the ta-C film in harsh environments.
Keywords: AMORPHOUS-CARBON FILMS; CATHODIC ARC; ION ENERGY; VACUUM-ARC; NANOINDENTATION